Research and realities politics in the Third World - Rebullida, Ma. Lourdes G. Genato (Diliman, Quezon City University of the Philippines Press, 2020)
"The Third world perspectives on politics series draws together scholarly articles from Kasarinlan: Philippine journal of third world studies ..."--Page preceding title page.
Third world, a definition / Pablo Gonzales Casanova -- Exotic love at your fingertips, intermarriage websites, gendered representation, and the transnational migration of Filipino and Thai women / Leonora Angeles and Sirijit Sunanta -- Politics and the media in Malaysia / Mustafa K. Anuar -- Three years of Indigenous Peoples Rights Act / Nestor T. Castro -- Analyzing NGO discourses / Josephine C. Dionisio -- The Philippine Armed Forces / Ricardo T. Jose -- Globalization, migration, and class struggles / Lisa Law and Kathy Nadeau -- An analysis of the seventeenth general elections in South Korea / Park Young-key -- The true results of the 2004 Philippine presidential elections based on the NAMFREL tally / Roberto Verzola.
Includes bibliographical references.
Keywords: Philippines -- Politics and government; Southeast Asia -- Politics and government; Developing countries -- Politics and government; Developing countries -- Social conditions